CURRENT STATUS OF PHYSICAL ACTIVITY AND SOME FACTORS RELATED TO ENOUGH PHYSICAL ACTIVITY IN DIABETES AT LONG HO DISTRICT HEALTH CENTER, VINH LONG PROVINCE IN 2021 (Vietnam Journal of Community Medicine, 2021)
Objectives: To determine the rate of physical activity and some associated factors between adequate physical activity and understanding, barriers, and support from family and friends in diabetic patients at the Long Ho district Health Center in Vinh Long province in 2021.Subjects and research methods: A cross-sectional descriptive study with analysis. The toolkit is based on the GPAQ (Global Physical Activity Questionnaire) questionnaire and related research [9].Results and discussions: Patients with incorrect knowledge about diabetes accounted for 53%, with sufficient physical activity 43.6%. The results of multivariable logistic regression analysis showed that there were relationship between sufficient physical activity and age (p
Keywords: Patients, diabetes, sufficient physical activity